Price Distortions, Exports, and Economic Growth: Evidence from the Non-Oil Sectors of Nigeria - Akanegbu, Benedict N (International Journal of Management and Sustainability, 2013)
This study examines the effects of price distortions on output in the non-oil sectors of the Nigerian economy. Specifically, the study tests the hypothesis: that price distortions are inversely related to non-oil output on the supply side; and also inversely related to the aggregate demand component such as non-oil exports on the demand side. The study adopts a model based on a modified neoclassical production function where non-oil exports are taken as production input. The analysis confirms the view that price distortions have significant negative influence on the non-oil sectors of the Nigerian economy.